Molecular dynamics simulation and phase transitions of Tetrafluoromethane - Abdulshahid, Rasha Ibrahim (AUC Knowledge Fountain, 2013)
Properties of material under extreme conditions, whether high pressures, high temperatures or low temperatures, are rather interesting. Understanding the properties of any given material at such extreme conditions provides a much clearer conception of the properties of this material in general. Although until recently studying the nature of matter under such extreme conditions was not possible via the traditional experimental or traditional methods, it was made possible by the utilization of computer simulation methods. Carbon tetrafluoride has been gaining wide interest in recent years due to its important role in the semiconductor processing industries. It is one of the most preferred etchants used today on a number of different silicon films. The importance of CF4 has resulted in a vast interest in studying the molecule under all possible conditions of pressure and temperature. The nature of CF4, it's crystal structure and phase transitions was investigated from 0 K to 450 K and from 0 GPa to 35 GPa, using the Molecular Dynamics simulation technique. Keith Refson's Moldy was the software we decided to use in our research. The results we were able to arrive at were compared with experimental findings and they were quite in agreement.